Treatment of Poor Sperm Quality and Erectile Dysfunction With Oral Pentoxifylline: A Systematic Review - Lu, Yi; Su, Hao; Zhang, Jianzhong; Wang, Yutao; Li, Hongjun (Frontiers in Pharmacology, 2022)
Background: Pentoxifylline (PTX) is a member of methylxanthine chemicals and a type of non-selective phosphodiesterase-5 inhibitors, which has been used in male-infertility treatment to improve sperm quality as well as for erectile dysfunction (ED) treatment. Mutually tight associations existed between ED and male-infertility, using PTX might kill two birds with one stone by improving sperm quality and erectile function in infertile men with ED Methods: PubMed, Cochrane Library, EMBASE, and Web of Science were searched by October 2021. Based on available evidence from both observational studies and randomized-controlled trails (RCTs), we conducted a systematic review to summarize the efficacy and safety of PTX in treating ED and male-infertility. The protocol of the paper was registered and updated in PROSPERO (CRD42021291396). Results: From 202 records, eight studies (7 RCTs) evaluating the role of PTX in ED and three studies (2 RCTs) assessing the efficacy of PTX in male-infertility were included in the systematic review. 3 studies (100.00%) and 2 studies (100.00%) reported the advantageous role of PTX in improving sperm progressive motility and normal sperm morphology rate, respectively, while only 1 study (33.33%) indicated the favorable role of PTX in enhancing sperm concentration. As for ED, 3 (60.00%) studies supported the treatment role of PTX alone in ED and 2 studies (66.67%) favored the combination use of PTX and selective PDE5Is compared with selective PDE5Is alone. Safety analysis showed that PTX was a well-tolerated drug in both ED and male-infertility treatment. Conclusion: Given the association between ED and male-infertility and satisfying findings achieved from available evidence, PTX administration for the simultaneous treatment of poor sperm quality and mild ED in infertile men will highly enhance the treatment compliance. However, the finding should be treated carefully until it was validated by further studies.